Transactional or Transformational? Leadership Preferences of Division III Athletic Administrators - Laura J. Burton; Jon Welty Peachey (Journal of Intercollegiate Sport, 2009)
Leadership research within sport management has yielded inconsistent results when examining transactional and transformational leadership. In addition, there has been a paucity of research comparing leadership behaviors between men and women based on leadership style. Therefore, this study examined whether leadership style (transactional, transformational) led to more positive perceptions of organizational outcomes in intercollegiate athletic administration and whether gender of the leader influenced these perceptions of leaders. Ninety-eight Division III athletic directors evaluated either a male or female transactional leader or a male or female transformational leader on extra effort, effectiveness, and satisfaction. Findings indicated transformational leadership was related to more positive organizational outcomes, specifically extra effort and satisfaction. However, gender of the leader did not influence these perceived outcomes.